Efficacy of a heat mitigation strategy on gait in prolonged load carriage - Tay, Cheryl Sihui. (2013)
This study compared the gait characteristics of participants in a military prolonged load carriage protocol (PLC) while ingesting water (CON) versus ice slurry (ICE) as a heat mitigation strategy. 7 heat acclimatised males volunteered for a 15 km loaded treadmill walk (30 kg) in an environmental chamber replicating tropical climatic conditions. Gait patterns were obtained from an optical gait measurement system (OptoGait, Microgate, Bolzano, Italy) and high-speed digital video for one minute at the start and end of two work-rest cycles. Gait variables included stance time, swing time, double support time, step length and step width (SW). Variability was defined as the standard deviation (SD) and coefficient of variation (CV). Univariate repeated measures (a = 0.05) compared gait variables across time and between conditions. Relationships between selected gait and physiological variables were examined through Pearson product moment correlation. Gait characteristics and gait variability (p = .001 to .035) indicated a more stable walking pattern in ICE compared to CON, while mean SW had a main effect of time (p = .019) and interaction (p = .017), step width CV had interaction effects (p = .041), and percentage of crossover steps had both main effects of time (p = .022) and condition (p = .039). Correlations between the latter three variables and body core temperature (Tc) and heart rate (HR) responses were low/moderate. In summary, ice slurry is potentially effective in inducing a more stable gait pattern. Future PLC studies may further integrate biomechanical and physiological outcomes through non-linear analysis.